You need to solve this equation for x: ax−7=26
Which would be the best first step you could make to solve the equation?
Combine ax - 7 to get -7x
divide ax by a and 26 by a
add 7 to both sides of the equation
subtract 7 from the left side of the equation
5 answers
To solve the equation ax - 7 = 26 for x, the best first step would be to add 7 to both sides of the equation. This will eliminate the -7 term on the left side and simplify the equation.
You need to solve this equation for x: ax−7=26
Which would be the best first step you could make to solve the equation?
Combine ax - 7 to get -7x
divide ax by a and 26 by a
add 7 to both sides of the equation
subtract 7 from the left side of the equation
Which would be the best first step you could make to solve the equation?
Combine ax - 7 to get -7x
divide ax by a and 26 by a
add 7 to both sides of the equation
subtract 7 from the left side of the equation
Apologies for the confusion in the previous response. The best first step to solve the equation ax - 7 = 26 for x would be to add 7 to both sides of the equation.
The correct first step would be:
Add 7 to both sides of the equation:
ax - 7 + 7 = 26 + 7
This simplifies to:
ax = 33
The correct first step would be:
Add 7 to both sides of the equation:
ax - 7 + 7 = 26 + 7
This simplifies to:
ax = 33
fill in the blanks to follow the steps in solving the equation: 5x−12−6x=−10x+7−1
5x−12−6x=−10x+7−1
Step 1: Combine like terms Response area,
Step 2: Get x-terms on same side of equation Response area
Step 3: Get constants on same side of equation Response area
Step 4: Get the x by itself by using the inverse operation Response area
5x−12−6x=−10x+7−1
Step 1: Combine like terms Response area,
Step 2: Get x-terms on same side of equation Response area
Step 3: Get constants on same side of equation Response area
Step 4: Get the x by itself by using the inverse operation Response area
5x - 12 - 6x = -10x + 7 - 1
Step 1: Combine like terms
Starting equation: 5x - 12 - 6x = -10x + 7 - 1
Combining like terms on the left side: -x - 12 = -10x + 7 - 1
Step 2: Get x-terms on same side of equation
Starting equation: -x - 12 = -10x + 7 - 1
Adding 10x to both sides: -x + 10x - 12 = -10x + 10x + 7 - 1
Simplifying: 9x - 12 = 7 - 1
Step 3: Get constants on same side of equation
Starting equation: 9x - 12 = 7 - 1
Adding 12 to both sides: 9x - 12 + 12 = 7 - 1 + 12
Simplifying: 9x = 18
Step 4: Get the x by itself by using the inverse operation
Starting equation: 9x = 18
Dividing both sides by 9: 9x/9 = 18/9
Simplifying: x = 2
The solution to the equation is x = 2.
Step 1: Combine like terms
Starting equation: 5x - 12 - 6x = -10x + 7 - 1
Combining like terms on the left side: -x - 12 = -10x + 7 - 1
Step 2: Get x-terms on same side of equation
Starting equation: -x - 12 = -10x + 7 - 1
Adding 10x to both sides: -x + 10x - 12 = -10x + 10x + 7 - 1
Simplifying: 9x - 12 = 7 - 1
Step 3: Get constants on same side of equation
Starting equation: 9x - 12 = 7 - 1
Adding 12 to both sides: 9x - 12 + 12 = 7 - 1 + 12
Simplifying: 9x = 18
Step 4: Get the x by itself by using the inverse operation
Starting equation: 9x = 18
Dividing both sides by 9: 9x/9 = 18/9
Simplifying: x = 2
The solution to the equation is x = 2.